Mobility of 90Sr and 137Cs in soils characterized with contrasting properties - Yu. O. Ivanov; S. E. Levchuk; Yu. V. Khomutinin; O. M. Kadygrib; L. V. Yoschenko; V. V. Pavliuchenko (Ядерна фізика та енергетика)
Results of the study of 90Sr and 137Cs migration mobility in soils characterized with contrasting physical-chemical properties and granulometric composition has been analyzed. The mentioned radionuclides were intro-duced in soils in initial water-soluble form. Ecological and effective half-time of cleaning of soils 20-cm hori-zons (Tecol) has estimated. Mean values of Tecol 90Sr varies in limits 3.7 - 84 years. Tecol 137Cs varies in limits 61 - 265 years. Correlation of ecological half-time cleaning of soddy-podsolic soils species from radionuclide and physical-chemical properties and granulometric composition of these ones has been analyzed, strong correlation of Tecol 90Sr as well, as mean correlation of Tecol137Cs with mentioned soils characteristics has been noted.